Evaluation of Near Infrared Dyes as Markers of P-Glycoprotein Activity in Tumors - Semenenko, Inessa; Portnoy, Emma; Aboukaoud, Mohammed; Guzy, Serge; Shmuel, Miriam; Itzhak, Gal; Eyal, Sara (Frontiers in Pharmacology, 2016)
Aim: The multidrug resistance protein 1 (MDR1; P-glycoprotein) has been associated with efflux of chemotherapeutic agents from tumor cells and poor patient prognosis. This study evaluated the feasibility of non-invasive, non-radioactive near infrared (NIR( imaging methodology for detection of MDR1 functional activity in tumors. Methods: Initial accumulation assays were conducted in MDR1-overexpressing MDCK cells (MDCK-MDR1) and control MDCK cells (MDCK-CT) using the NIR dyes indocyanine green (ICG), IR-783, IR-775, rhodamine 800, XenoLight DiR and Genhance 750, at 0.4 µM to 100 µM. ICG and IR-783 were also evaluated in HT-29 cells in which MDR1 overexpression was induced by colchicine (HT-29-MDR1) and their controls (HT-29-CT). In vivo optical imaging studies were conducted using immunodeficient mice bearing HT-29-CT and HT-29-MDR1 xenografts. Results: ICG’s emission intensity was 2.0- and 2.2-fold higher in control versus MDR1-overexpressing cells, in MDCK and HT-29 cell lines, respectively. The respective IR-783 control:MDR1 ratio was 1.4 in both MDCK and HT-29 cells. Optical imaging of mice bearing HT-29-CT and HT-29-MDR1 xenografts revealed a statistically non-significant, 1.7-fold difference (p>0.05) in ICG emission intensity between control and MDR1 tumors. No such differences were observed with IR-783. Conclusion: ICG and IR-783 appear to be weak MDR1 substrates. In vivo, low sensitivity and high between-subject variability impair the ability to use the currently studied probes as markers of tumor MDR1 activity. The results suggest that, for future use of this technology, additional NIR probes should be screened as MDR1 substrates.